Argumenter pour ou contre son opinion - Céline Beaudet; Denis Alamargot (Communication)
This research assesses how well students in professional communication succeed in writing an argumentative essay without introducing their personal beliefs. Content analysis shows that the emphasis is put on ethos and pathos rather than on logos, so as to influence the reader by appealing to his/her identification and emotions. Educational guidelines, designed to help students temper their own opinions, are proposed in conclusion.